Unveiling the Influences of Personality Traits, Self-efficacy, Parental Background, and Economic Situation on Entrepreneurial Despondency among Generation Z - Suryawirawan, Okto Aditya; Suhermin, Suhermin; Suwitho, Suwitho; Bon, Abdul Talib (Jurnal Aplikasi Manajemen, 2024)
The economic challenges faced by Indonesia for the past couple of years, including substantial losses and a rise in bankruptcies, coupled with the ongoing impact of global tensions between Russia and Ukraine, underscore the crucial role of entrepreneurs in mitigating unemployment and fostering economic recovery. This study uses non-probability purposive sampling towards 205 students. This study uses partial least square through SmartPLS to analyze the results. The research examined the relationship between personality traits, self-efficacy, parental background, economic situation and entrepreneurial despondency among Generation Z. Among personality traits dimensions, risk-taking propensity was found to have no impact on entrepreneurial despondency, innovativeness was found to have no impact on entrepreneurial despondency, and optimism was found to have a negative impact on entrepreneurial despondency. Self-efficacy found to have a negative impact on entrepreneurial despondency. The impact of risk-taking propensity, innovativeness and optimism on entrepreneurial despondency were mediated by self-efficacy. Parental background was found to have no impact on entrepreneurial despondency and did not moderate the effect of self-efficacy on entrepreneurial despondency. Economic situation was found to have a negative impact on entrepreneurial despondency but failed to moderate the effect of self-efficacy on entrepreneurial despondency. These findings contribute to the theoretical understanding of the factors influencing Generation Z's entrepreneurial intentions, offering insights for educators and policymakers seeking to enhance Generation Z's entrepreneurial inclination.